Implications of tolerance to iron toxicity on root system architecture changes in rice (Oryza sativa L.) - Sonu,; Nandakumar, Shekharappa; Singh, Vikram Jeet; Pandey, Rakesh; Gopala Krishnan, Subbaiyan; Bhowmick, Prolay Kumar; Ellur, Ranjith Kumar; Bollinedi, Haritha; Harshitha, Bheemapura Shivakumar; Yadav, Sunaina; Beniwal, Ravina; Nagarajan, Mariappan; et al. (Frontiers in Sustainable Food Systems, 2024)
Introduction Toxicity due to excess soil iron (Fe) is a significant concern for rice cultivation in lowland areas with acidic soils. Toxic levels of Fe adversely affect plant growth by disrupting the absorption of essential macronutrients, and by causing cellular damage. To understand the responses to excess Fe, particularly on seedling root system, this study evaluated rice genotypes under varying Fe levels. Methods Sixteen diverse rice genotypes were hydroponically screened under induced Fe levels, ranging from normal to excess. Morphological and root system characteristics were observed. The onset of leaf bronzing was monitored to identify the toxic response to the excess Fe. Additionally, agronomic and root characteristics were measured to classify genotypes into tolerant and sensitive categories by computing a response stability index. Results Our results revealed that 460 ppm of Fe in the nutrient solution served as a critical threshold for screening genotypes during the seedling stage. Fe toxicity significantly affected root system traits, emphasizing the consequential impact on aerial biomass and nutrient deprivation. To classify genotypes into tolerant and sensitive categories, leaf bronzing score was used as a major indicator of Fe stress. However, the response stability index provided a robust basis for classification for the growth performance. Apart from the established tolerant varieties, we could identify a previously unrecognized tolerant variety, ILS 12–5 in this study. Some of the popular mega varieties, including BPT 5204 and Pusa 44, were found to be highly sensitive. Discussion Our findings suggest that root system damage, particularly in root length, surface area, and root volume, is the key factor contributing to the sensitivity responses under Fe toxicity. Tolerant genotypes were found to retain more healthy roots than the sensitive ones. Fe exclusion, by reducing Fe2+ uptake, may be a major mechanism for tolerance among these genotypes. Further field evaluations are necessary to confirm the behavior of identified tolerant and sensitive lines under natural conditions. Insights from the study provide potential scope for enhancement of tolerance through breeding programs as well as throw light on the role root system in conferring tolerance.